Upper bound analysis of the anti-seismic stability of slopes considering the effect of the intermediate principal stress - Zhang, Biao; Sun, Quanli (Frontiers in Earth Science, 2023)
Considering the intermediate principal stress effect of soils, the unified strength theory was applied to correct the shear strength index of soils. Based on a mechanical model of anti-seismic stability of slopes, the analytical formula of stability coefficient was deduced by the upper bound method and the quasi-static method. And then the optimal solution of stability coefficient was figured out via the Matlab software. The result shows that, if the intermediate principal stress was ignored, the shear strength of soils would obviously be underestimated, so did the slope stability coefficient, the relative error of that can reach 39.87%. The horizontal and vertical seismic forces significantly affect the slope stability. When the horizontal seismic force is considered, the slope stability coefficient Ns is reduced by 79.82%. Similarly, if the seismic effect was not neglected, the stability of the slope will be seriously overestimated. Slope cutting can significantly improve the slope stability. While the slope angle is reduced from 90° to 50°, the stability factor increases by 279.82%. The reasonable design slope angle is between 50° and 60° when slope safety and economics are taken both into account.